Pengendalian Pemanfaatan Ruang Berbasis Kinerja Jalan Pada Fungsi Primer di Perkotaan Garut - Jajan Rohjan; Andi Harmaen Hanafi (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2016)
Otista road in Garut is the function of primary collector road that connects between Garut and Tasikmalaya regency of Bandung regency, and serve the movement from within and outside Garut. Because of its role as one of the entrance-exit from / to Garut and the amount of traffic load and high intensity continuous movement, this road has resulted in an imbalance in the supply and demand of transport in the region and lead to delay movement, consequently the burden of road corridor Otista becomes heavier and its performance as a primary collector roads are decreasing. This study aimed to optimize the performance of the way through the control of space utilization in urban areas Garut using the Highway Capacity Manual (MKJI 1997). The data used for the analysis is obtained by means of collecting primary data and secondary data collection according to the needs of research. Data analysis was conducted on the analysis of the intensity of use of space, the analysis of traffic volume, the amount of analysis generation and analysis of vehicle traction performance of the road. From the results of the analysis showed that the volume of vehicles on the road corridor Otista Garut is not comparable to the capacity of the existing road, with the level of service at the level that level of service D